Fuel property estimation and combustion process characterization : conventional fuels, biomass, biocarbon, waste fuels, refuse derived fuel, and other alternative fuels - Kiang, Yen-Hsiung, 1947- (Academic Press, an imprint of Elsevier, 2018)
Fuel Property Estimation and Combustion Process Characterization is a thorough tool book, which provides readers with the most up-to-date, valuable methodologies to efficiently and cost-effectively attain useful properties of all types of fuels and achieve combustion process characterizations for more efficient design and better operation. Through extensive experience in fuels and combustion, Kiang has developed equations and methodologies that can readily obtain reasonable properties for all types of fuels (including wastes and biomass), which enable him to provide guidance for designers and operators in the combustion field, in order to ensure the design, operation, and diagnostics of all types of combustion systems are of the highest quality and run at optimum efficiency. Written for professionals and researchers in the renewable energy, combustion, chemical, and mechanical engineering fields, the information in this book will equip readers with detailed guidance on how to reliably obtain properties of fuels quickly for the design, operation and diagnostics of combustion systems to achieve highly efficient combustion processes. Presents models for quick estimation of fuel properties without going through elaborate, costly and time consuming sampling and laboratory testingOffers methodologies to determine combustion process characteristics for designing and deploying combustion systemsExamines the fundamentals of combustion applied to energy systems, including thermodynamics of traditional and alternative fuels combustionPresents a fuel property database for over 1400 fuelsIncludes descriptive application of big data technology, using dual properties analysis as an exampleProvides specific technical solutions for combustion, fuels and waste processing.